Effect of assembly construction on the wind induced pressure of membrane roofs. (15th October 2020) - Chavez, Mauricio; Baskaran, Appupillai; Feng, Changda; Gan Chowdhury, Arindam
Abstract: In North America over 60% of low slope buildings are roofed with membranes, and the market survey indicates that there is continuous growth in such roof assemblies. To the best knowledge of the authors, there is no in-situ measured data from such roofs. The National Research Council of Canada (NRCC), in collaboration with the Special Interest Group on Dynamic Evaluation of Roofing Systems (SIGDERS) consortium, has undertaken an in-situ monitoring program with the goal of providing valuable data to benchmark the current code provisions, as well as providing supporting data for existing wind uplift test methods to determine roof cladding resistance. This paper presents in-situ data of two most common commercial roof systems: mechanically attached roof system (MARS) and partially adhered roof system (PARS) and provides side-by-side comparison (partially refers to a system with and adhered membrane over some components that are mechanically attached). In order to provide more detail and controllable measurements, MARS and PARS mock-ups were evaluated at the open flow NHERI Wall of Wind (WOW) Experimental Facility (EF) at Florida International University (FIU). The investigations included visual observations (video) and pressure measurements at different roof locations in various wind directions and wind speeds. The visual observations confirmed that, due to construction characteristic, the membrane of the MARS deforms (balloons) under wind suction. The field and WOW pressure measurements revealed that the MARS generates systematic lower peaks pressure in comparison with the PARS. Data from field showed that the average reduction of the MARS is in the order of 20% in comparison to the PARS at locations close to the leading edge when wind is NW and WNW (close to normal). The WOW results showed that the pressure reduction of the MARS is in average 16% in comparison to the PARS when wind is W (normal), and the reduction would decrease to 12% when considering the worst case among all the wind directions tested in the lab.